IMPACT OF INTERNAL SHADING CONTROLS ON EFFICIENT DAYLIGHTING IN HOME-OFFICE WORKSPACES IN TROPICAL CLIMATES (Jurnal Teknologi (Sciences & Engineering), 2021)
Home office workspaces have significantly grown in residential sectors throughout the world. Nowadays, many people worldwide are forced to work from their housing units due to the outbreak of the COVID-19 pandemic. However, the existing residential buildings were only designed for living activities, not for desk-related tasks. This is more critical in tropical regions with the overabundance of indoor daylight and lack of external shadings on existing buildings. Despite the limitations for modifying the external facades, interior retrofit plays a major role in improving visual environments. Daylighting performances of various configurations, including internal shading devices, interior surfaces, and window films, were experimented with the Radiance-IES program. A field measurement of daylight was conducted in a home office room under the Malaysian tropical sky to validate the simulated results. This research proved that the existing residential buildings in the tropical climates had poor daylighting performance where the mean indoor illuminance could be over 10,000 lx. The combination of a light shelf, a partial blind, and the tinted window film could effectively 85% alleviate the excessive indoor daylight level. This configuration recorded a significant improvement in Useful Daylight Zone (around 300%), and Daylight Glare Probability was considerably reduced from 0.46 to 0.34.